Isolation, characterization and optimization of chrysene degradation using bacteria isolated from oil-contaminated water - Smeera Thomas (IWA Publishing, 2021)
Polyaromatic hydrocarbons (PAHs) are uncharged, non-polar molecules generated from natural and anthropogenic activities, where the emissions from anthropogenic activities predominate. Chrysene is a high molecular weight PAH, which is found to be highly recalcitrant and mutagenic in nature. The aim of this study was to isolate chrysene-degrading microorganisms from oil-contaminated water and to enhance their degradative conditions using design expert. From the various samples collected, 19 bacterial strains were obtained through enrichment culture and the one which showed highest activity was identified by 16S rRNA sequencing as Bacillus halotolerans. Under optimum conditions of 100 mg/L chrysene concentration, 1,000 mg/L nitrogen source, and pH 6, B. halotolerans exhibited 90% chrysene degradation on sixth day. Positive results for the enzymes laccase and catechol 1,2 dioxygenase confirmed the ability for chrysene degradation by the isolated strain. Major metabolic intermediate determined in gas chromatography-mass spectrometry (GCMS) analysis was diisooctyl phthalate. Hence it can be concluded that B. halotolerans can be a promising candidate for the removal of high molecular weight (HMW) hydrocarbons from contaminated environments. HIGHLIGHTS Bacterial strain capable of degrading chrysene was isolated and sequenced.; Operational conditions like carbon source, nitrogen, pH and incubation period were optimized using design expert software to ensure maximum degradation.; It has been demonstrated that Bacillus halotolerans can mineralize chrysene to fewer toxic forms like catechol and phthalic acid derivatives.;